El matrimonio igualitario y sus efectos en el interés superior del niño - Asanza Álava, Melissa Lilibeth (2020)
In Ecuador, equal marriage has triggered an infinity of doubts and queries that have not yet been answered, in fact, despite having adopted the decision by the Constitutional Court, it is not established, nor regulated by the Constitution of the Republic of Ecuador. Said marriage and therefore the adoption for this creation of new families, is not allowed, because as established in article 68 of the Constitution of the Republic of Ecuador that literally says that: "The adoption will correspond only to couples of different sex”. It is for this reason that our investigative concern arises as to how adoption would behave within equal marriage, since obviously it contrasts with the principles of equality of people before the law, but above all with the principle of the best interests of the minor, and, depriving both of their rights, such as having a family based on Law, and that the boy, girl or adolescent enjoy their respective Rights and principles. It is emphasized to clarify that the Ecuadorian legal system does not guarantee the rights or principles adherent to the human being and to children and adolescents, due to two Ecuadorian legal institutions such as Marriage and Adoption.............